Organosilanes and polypyrrole as anticorrosive treatment of aluminium 2024 - Correa-Borroel, A. L.; Gutierrez, S.; Arce, E.; Cabrera-Sierra, R.; Herrasti, P. (Journal of applied electrochemistry, 2009)
This paper addresses the preparation and characterisation of anticorrosive silane- and polypyrrole-based organic coatings and combinations of the two on aluminium 2024. Layer adsorption studies of organosilanes such as propyl (C3), octyl (C8) and octadecyl (C18) trimethoxysilane and polypyrrole deposits on the aluminium electrodes reveal only limited protection. Their anticorrosive power declines when they are subject to highly corrosive environments, such as salt fog cabinets, for extended periods. The combination of both deposits yields a more protective structure that affords better protection with time. The best performance is achieved with polypyrrole deposits on silanes due to the excellent bonding between the silane adsorbed on the surface of the material and the polypyrrole film. Of the three organosilanes used, the one with the shortest chain performs best. When long-chain organosilanes are used, the polypyrrole film becomes detached due to the lesser interaction between the layers. Electrochemical impedance spectroscopy and morphological studies of the layers also show the greater adhesion and lesser deterioration of polypyrrole deposits on silane layers.